1989
DOI: 10.1021/ac00182a008
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared least-squares methods for the quantitative analysis of multicomponent mixtures of airborne vapors of industrial hygiene concern

Abstract: Air monitoring methods suitable for use in the workplace, though accurate for monitoring individual compounds or classes of compounds, cannot be used to monitor several compounds or classes of compounds simultaneously. In the past few years, Fourier transform infrared (FT-IR) spectroscopy has been investigated for use as a method for multicomponent quantitative analysis. This work focuses on quantitative analysis of six mixtures in ambient air. The concentration ranges of the two- to six-component mixtures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For traditional quantitative applications, where the identities of the components of the mixture are known, LSF approaches have been used with good success (23)(24)(25)(26)(27). As expected, Warner and co-workers found that the results of an analysis using LSF can be strongly affected by not including all components in samples.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For traditional quantitative applications, where the identities of the components of the mixture are known, LSF approaches have been used with good success (23)(24)(25)(26)(27). As expected, Warner and co-workers found that the results of an analysis using LSF can be strongly affected by not including all components in samples.…”
Section: Introductionmentioning
confidence: 79%
“…In this circumstance, it is extremely difficult to interpret IR spectra by using computerized techniques that depend on picking peaks. This is due to low peak intensities, "chemical noise", and electronic noise (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of vinyl chloride was unexpected in the incineration of ethyl chloride and illustrates the power of infrared absorption spectroscopy (30). Often multipoint regression analysis is used to obtain the best fit of cali- bration spectra of several species to the sample (31). This technique, however, works only when all of the species in a spectrum have been identified.…”
Section: Chlorinated Hydrocarbon Combustionmentioning
confidence: 99%
“…However, the multivariate calibration methods can efficiently resolve this problem. The typical multivariate calibration methods include classical least squares method (CLS) (Haaland et al,1985;Haaland,1987 andYing et al, 1989), inverse least squares method (ILS) (Brown et al, 1982 andBrown, 1986) , principal component regression (PCR) (Fredericks et al, 1985;Donahue et al, 1988 andSeasholz et al, 1989), partial least squares method (PLS) (Geladi et al, 1986a, Geladi et al, 1986band Seasholtz et al, 1989, Kaiman filter method (KFM) (Liu 1989;Poulisse 1979 andvan Veen et al, 1991), etc. Geladi et al(1986b) discussed the performance of PLS through the analysis of the mixture of two components.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al(1990) studied the comparison of four calibration methods including ILS, CLS, PLS and PCR with the computer simulation of calibration and prediction data sets for the mixture of three components. Ying et al( 1989) reported the research of CLS for hygiene concerns of six at large. The baseline, the background reference file and the optimal wave peak window were studied to evaluate the influence of the analytical results.…”
Section: Introductionmentioning
confidence: 99%